Effect of Giving Papaya Leaf Extract (Carica Papaya L.) on Changes in Fasting Blood Glucose in Male Wistar Rats (Rattus Norvegicus) Induced by Streptozotocin - Sudarisman, Gabriella Alisha; Sajuni Widjaja; Puri Safitri Hanum (International Journal of Medical Science and Clinical Research Studies, 2025)
Background: Diabetes mellitus is a disease characterized by an increase in blood glucose levels due to decreased insulin production or decreased insulin action. Diabetes cases are described as a serious problem globally in the 21st century and cases are increasing worldwide. One type of plant that can be used as a medicine is papaya leaf (Carica papaya L.) which is known to contain several active compounds such as flavonoids, saponins, tannins, and alkaloids. Objective: To determine the effect of papaya leaf extract (Carica papaya L.) on changes in fasting blood glucose levels of male Wistar rats with hyperglycemia conditions. Methodology: This research is an experimental research Randomized Controlled Trial (RCT) with Pretest-Postest Group Design study design. This study used 35 male white rats which were divided into 5 groups. Group I (without treatment), group II (STZ-NA), group III (STZ-NA and Glimepiride), group IV (papaya leaf extract at a dose of 150mg/Kg), group V (papaya leaf extract at a dose of 200mg/Kg). The data obtained after the study will be tested for normality which is then continued with non-parametric tests using the Kruskal-Wallis and Mann-Whitney U tests, and an effect size test is carried out to determine how much effect is produced from the papaya leaf extract given. Research Results: The administration of papaya leaf extract at a dose of 200mg/200grBody Weight in male Wistar rats in group 5 proved to reduce fasting blood glucose levels more significantly than the administration of glimepiride at a dose of 0.04 mg and papaya leaf extract at a dose of 150mg/Kg. Conclusion: Administration of papaya leaf extract (Carica papaya L.) can reduce fasting blood glucose levels in diabetic model rats effectively at a dose of 200mg/Kg.